Chasing the Ghost Bear : On the Trail of America's Lost Super Beast - Stark, Mike (Journalist) (Book collections on Project MUSE., 2022)
"Chasing the Ghost Bear explores modern research into one of the legendary but overlooked extinct mammals from the Pleistocene epoch, the short-faced bear. Mammoths and sabertoothed cats receive most of the popular attention, but these wide-ranging bears may have ruled the West prior to the Ice Age extinctions that left grizzlies and bison as the largest mammals of the American West"--